(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The Banking Supervision of the most important functions of the Central Bank of Iraq, which he intended to have a strong banking system and a sound and competitive, and exercised control over the banks by inspection bodies to ensure their compliance with the laws, regulations and orders and instructions and the safety of their financial positions. The research was aimed to release the concept of banking inspection, compliance and problems and obstacles faced by the inspectors, and monitors compliance and down to make recommendations. Has been reached on a set of theoretical and practical conclusions, including: - 1-confirmed the statistical analysis of the answers to the research sample the importance of the role of inspection in achieving compliance with banking, and this proves the hypothesis of research that indicates that the application of the provisions of the banking inspection will enable the banks to deal with distractions and negatives and enhance the pros in action.